Segregation of a t(3;20) translocation through three generations resulting in unbalanced karyotypes in six persons. Issue 5 (October 1986) - Nielsen, K B; Tommerup, N; Jespersen, B; Nygaard, P; Kleif, L
Abstract : With the aid of high resolution chromosome banding, a t(3;20) translocation was discovered in a large family with six retarded members. The translocation involved very small terminal segments. The unbalanced products resulting in partial trisomy 20q and monosomy 3p were observed in the retarded subjects. Gene localisation studies of the ADA gene, with a presumed locus on the long arm of chromosome 20, were also carried out and seem to exclude this gene from the distal part of 20q (20q13.1—-qter).